Selection of parameters using ground reaction force measurement and 3D motion capture for developing biomechanical feedback training in golf - Shan, G.; Betzler, N.; Zhang, X.; Yu, D. (Routledge handbook of ergonomics in sport and exercise, 2016)
One of sport medicine goals is to promote people to involve more physical activity in order to develop positive altitude and health lifestyle. Therefore, studies on developing effective human motor skill learning/training will benefit every one of us, as it can help us to develop interests to involve more physical activity during the life span (Chen and Ennis, 2004). Studies, especially the one led by Professor Dr Paffenbarger at Harvard University involving 50,000 alumni who graduated between 1916 and 1950, show that more active involvement in physical activity will achieve healthy ageing by increasing life expectancy and gaining disability-free years during senior time (Nusselder et al., 2008; Paffenbarger et al., 1986). These studies indicate that the two key factors for promoting population health are: (1) to identify types of physical activities that can cover large population (i.e. the popular sports) across all age groups; and (2) to develop effective training methods for the selected sports. Among the top 10 most popular sports played in the world (Chintu, 2012), golf is the only one widely participated by all age groups (Table 21.1). It is well known that the dominant skill in golf is the swing. Therefore, scientific studies on golf swing will benefit both the development of effective training methods and the promotion of population health.